Spatial Heterogeneity in Women’s Financial Inclusion in India: An application of small area estimation - Swati Srivastava; Kaushalendra Kumar; Lotus McDougal; Apoorva Nambiar; Ashish Kumar Upadhyay; Katherine Hay; Anita Raj; Abhishek Singh (PLoS ONE, 2026)
Background While India is making notable strides in women’s financial inclusion, closing remaining gaps is hampered by a lack of granular data at the sub-state level. This study uses model-based small-area estimation techniques, linking data of National Family Health Survey 2015−16 and 2019−21, respectively, with the 2011 Indian Census data to generate district-level estimates of three components of women’s financial inclusion: women’s bank/savings account ownership, their knowledge and use of microcredit programmes in 640 districts of India in 2015−16 and 2019−21. Results Model-based estimates reveal considerable intra- and inter-state variations in all indicators. In NFHS-5, estimates of bank/savings account ownership varied from 56.1% in Kiphire district of Nagaland to 95.4% in Perambalur district of Tamil Nadu. Knowledge of microcredit programmes varied from 11.8% in Lawngtlai district of Mizoram to a maximum of 84.9% in Thiruvarur district of Tamil Nadu. The use of microcredit programmes was more limited (7.7%). Substantial within state clustering was present in all the three components. Districts with lower prevalences in NFHS-4 registered higher increase between NFHS-4 and NFHS-5 in women’s bank/savings account ownership and their knowledge of microcredit programmes. Conclusions Present study reveals considerable intra-state variations in both rates of financial inclusion and changes in financial inclusion levels over time. Our approach provides a new tool for policy makers to identify and close remaining gaps in women’s financial inclusion.